IoT Enabled Wearable Device for COVID Safety and Emergencies - Rao, Santhosha (International Journal of Interactive Mobile Technologies (iJIM), 2021)
The worldwide outbreak of COVID-19 has significantly changed the mindset of the people and over the period they started practicing healthy lifestyle to contain the spread of the virus. Despite this, increase in the number of cases and death rates across the globe are major cause of concern. In addition to maintaining the healthy lifestyle it is also essential to exploit the technological advancements in the field of Internet of Things (IoT) in designing a cost-effective wearable device which could possibly indicate the early stages of virus infection. In this work, a low cost IoT enabled wearable device is designed which generates alerts in case of any of the measured parameter goes out of the normal range besides sending notifications.